National legal interventions in overcoming underage marriages in indigenous communities - Tan, Winsherly; Agustini, Shenti; Agustianto, Agustianto (Jurnal Hukum Novelty, 2024)
Introduction to The Problem: Marriage is everyone's right. However, the phenomenon that occurs is the practice of underage marriage, this also occurs in the indigenous community of the Orang Laut tribe in Lingga Regency.Purpose/Objective Study: The aim of this research is to analyze the regulation of national law and customary law in dealing with underage marriage in the Orang Laut tribal community and to find a concept of legal harmonization that can resolve the practice of underage marriage.Design/Methodology/Approach: The research method used is empirical juridical. The type of data sourced from primary data is through observation and interviews as well as primary data. The basic theories used are the Theory of Legal Work and the Theory of Development Law.Findings: The results of the research state that there is a regulatory inconsistency between marriage law and child protection law. The marriage law allows for underage marriages by applying for dispensation, while Article 26 of the child protection law strictly stipulates that parents are obliged to prevent child marriages from occurring. And there is a culture of "reciprocation" which is the basis for the Sea People tribe to perpetuate the practice of underage marriage. In fact, marriages are only carried out through traditional ceremonies and according to their respective religions without applying for dispensation to the court. This means that the marriage carried out is only valid according to custom and religion and is not legally valid. Therefore, it is necessary to harmonize the law with an institutional approach in overcoming the phenomenon of underage marriage in the indigenous people of the Orang Laut tribe, Lingga Regency.Paper Type: Research Article